Real-world characteristics of women with endometriosis-related pain entering a multidisciplinary endometriosis program - Sanjay K. Agarwal; Oscar Antunez-Flores; Warren G. Foster; Ashwaq Hermes; Shahrokh Golshan; Ahmed M. Soliman; Amanda Arnold; Rebecca Luna (BMC, 2021)
Abstract Background Women with endometriosis are commonly treated by their sole provider. In this single-provider model of care, women frequently report long diagnostic delays, unresolved pelvic pain, multiple laparoscopic surgeries, sequential consultations with numerous providers, and an overall dissatisfaction with care. The emergence of multidisciplinary endometriosis centers aims to reduce diagnostic delays, improve pain management, and promote patient satisfaction; however, baseline data at the time of presentation to a multidisciplinary center are lacking. Methods A real-world, retrospective, single-site, cross-sectional study of women with surgically confirmed and/or clinically diagnosed endometriosis generated baseline data for a planned longitudinal assessment of multidisciplinary care of endometriosis. The primary objective was to determine the proportion of patients experiencing mild, moderate, or severe pain for dysmenorrhea, non-menstrual pelvic pain (NMPP), and dyspareunia at entry into a multidisciplinary endometriosis clinic. Also explored were relationships between pain scores and clinical endpoints obtained from electronic medical records. Results More than half (59%) of the study participants (n = 638) reported experiencing pelvic pain for ≥ 5 years. Pain intensity was highest for patients reporting dysmenorrhea, followed by NMPP, and dyspareunia. Significant correlations were observed between total pelvic pain and patient age (r = -0.22, p < 0.001, n = 506) and number of previous healthcare providers (r = 0.16, p = 0.006, n = 292); number of previous providers and duration of pain (r = 0.21, p = < 0.0001, n = 279); and duration of pain and years since diagnosis (r = 0.60, p < 0.001, n = 302). Mean pain scores differed significantly by age group for dysmenorrhea (p < 0.001), NMPP (p = 0.005), and total pelvic pain (p < 0.001), but not for dyspareunia (p = 0.06), with the highest mean pain scores reported among those < 30 years of age. Conclusion These real-world data indicate that in the single-provider model of care, unresolved pelvic pain is common among women with endometriosis. Alternative care models, including a multidisciplinary approach, need to be evaluated for improvements in clinical outcomes. These data also highlight the importance of addressing NMPP, which may be particularly troublesome for patients.